Diffusion-Weighted MR Imaging ofGlobal Cerebral Anoxia - Arbelaez, Andres; Castillo, Mauricio; Mukherji, Suresh K. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Diffuse cerebral anoxia is a devastating event, and its acute findings, as revealed by conventional MR imaging and CT scanning, may be subtle. We analyzed diffusion-weighted and conventional MR images of patients with diffuse cerebral anoxia to determine their usefulness in establishing the diagnosis during the acute period and in determining the age of insult.METHODS: We reviewed 11 MR imaging studies of 10 patients who had experienced prolonged cardiac arrest. All of the patients underwent echo-planar diffusion-weighted imaging with low- and high-strength B values and multiplanar unenhanced MR imaging. We considered bright areas on the high-strength diffusion-weighted images to be abnormal when compared with low-strength images. Special attention was given to the cortex, basal ganglia, thalami, hippocampi, cerebellum, and white matter. Conventional MR studies also were reviewed, and abnormalities noted. The medical records of all of the patients were reviewed.RESULTS: Four patients who underwent imaging during the acute period (<24 hours) had bright basal ganglia (n = 2), bright cerebellum (n = 3), and bright cortex (n = 1) shown on their diffusion-weighted images. For these patients, conventional MR images showed questionable increased T2-weighted signal intensity in the basal ganglia (n = 1), and the results of two studies were judged to be normal. During the early subacute period (24 hours–13 days), four patients were studied, and were determined to have an abnormal cortex (n = 3) and basal ganglia (n = 2). For two of these patients, conventional MR images showed similar abnormalities, and the results of one study were normal. For two patients who underwent imaging during the late subacute period (14–20 days), diffusion-weighted images showed abnormalities mostly confined to white matter. Two patients who underwent imaging during the chronic phase (>21 days) had normal results of their diffusion-weighted imaging and one had evidence of laminar necrosis revealed by conventional MR imaging.CONCLUSION: During the acute period, high-strength diffusion-weighted images showed the abnormal basal ganglia, cerebellum, and cortex to a better extent than did conventional MR images. During the early subacute period, gray matter abnormalities were seen on diffusion-weighted images. During the late subacute period, diffusion-weighted images showed mostly white matter abnormalities. During the chronic stage, the results of diffusion-weighted imaging were normal. Our findings suggest that diffusion-weighted images are helpful for evaluating and dating diffuse cerebral anoxia, and therefore aid in the determination of prognosis and management of these patients.